Identifikasi Bakteri Patogen Pada Ikan Nila (Oreochromis niloticus) di Danau Batur, Bali - Angreni, Ni Putu Wiwin; Arthana, I Wayan; Suryaningtyas, Endang Wulandari (Current Trends in Aquatic Science, 2018)
This research aims to determine types of pathogen bacteria presented in body parts (liver and kidneys) of Tilapia ( Oreochromis nilotics ), types of bacteria attacks wild Tilapia and fish in Floating Culture Net (FCN) of Batur Lake as well as its prevalence bacteria found in Tilapia on Batur lake. Method used in this research is descriptive method, with a sampling method based on purposive sampling technique. According to identification’s result obtained, types of bacteria that infect liver were including to Aeromonas hydrophila , Plesiomonas shigelloides and Citrobacter freundii bacteria. Meanwhile, bacteria that infect kidneys are Aeromonas hydrophila , Aeromonas caviae , Plesiomonas shigelloides and Citrobacter freundii . Bacteria that infect wild fish are Aeromonas hydrophila , Aeromonas caviae and Plesiomonas shigelloides , while fishes in FCN are infected by Aeromonas hydrophila , Aeromonas caviae , Plesiomonas shigelloides and Citrobacter freundii bacteria. Infection prevalence of pathogen bacteria in Tilapia in Batur Lake is Aeromonas hydrophila at 55,5%, Plesiomonas shigelloides for 27,7%, Aeromonas caviae and Citrobacter freundii at 11,1%. According to sampling location, prevalence of bacteria that attacks wild fish are Aeromonas hydrophila and Plesiomonas shigelloides at 44,4%, Aeromonas caviae for 11,1%. Prevalence of bacteria that attacks fish in FCN is Aeromonas hydrophila for 66,6%, Citrobacter freundii infection at 22,2%, Aeromonas caviae and Citrobacter freundii at 11,1%.